The association of vitamin D, semen parameters, and reproductive hormones with male infertility: A cross-sectional study - Leila Maghsoumi-Norouzabad; Maryam Labibzadeh; Ahmad Zare Javid; Seyed Ahmad Hosseini; Gholam Abbas Kaydani; Maryam Dastoorpur (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: The prevalence of vitamin D deficiency and male infertility is high in Iran. Objective: The present research aimed to examine the association between serum vitamin D [25(OH)D], parameters of semen including semen volume, sperm count, motility and morphology, and reproductive hormones in infertile Iranian men. Materials and Methods: This was a cross-sectional study on 119 infertile men conducted between September 2018 and May 2019. Subjects were divided into 3 groups based on serum vitamin D levels: deficient ( < 10 ng/mL), insufficient (10 ng/mL ≤ 25(OH)D ≤ 30 ng/mL), and sufficient ( > 30 ng/mL). Body mass index and waist circumference were measured. 25(OH)D, testosterone, sex hormone-binding globulin, luteinizing hormone (LH), follicle-stimulating hormone and estradiol levels, and semen parameters were assessed. Results: The semen volume, sperm counts, total and progressively motile sperm, normal sperm morphology, testosterone levels, and testosterone/estradiol ratio were substantially higher in the sufficient group compared to the other groups (p < 0.001). Also, in the sufficient group, serum LH (p < 0.001) and estradiol (p < 0.001, p = 0.01) were notably lower and serum sex hormone-binding globulin (p < 0.001) and the testosterone/LH ratio (p < 0.001) were considerably higher compared to the insufficient and deficient groups. Conclusion: Our study showed a positive relationship between serum vitamin D levels, and seminal parameters and sex hormones in Iranian infertile males.